The Role of Education and Economic Activity in Poverty Reduction in Central Java Province - Musyarofah Nilal Muna (Universitas Islam Negeri Alauddin Makassar, 2026)
In the development of regions, poverty remains a persistent challenge, particularly in Central Java Province from 2020 to 2024, reflecting the changes associated with recovery from the pandemic. This study aims to explore how education, the LFPR, and the GRDP influence poverty levels. It utilizes data from 35 districts and cities over a five-year period (2020–2024), employing a quantitative approach, which yields 175 data points. The information was sourced from BPS and analyzed using panel data regression, with the fixed effects model chosen for the analysis. The results indicate that education does not have a significant impact on poverty levels. Conversely, the LFPR and GRDP have a significant negative relationship with poverty, indicating that increased workforce involvement and improved economic performance in the region contribute to reducing poverty. These results suggest that efforts to lessen poverty in Central Java rely more on job market trends and economic growth rather than solely on formal education. Therefore, government programs should focus on creating jobs, improving access to the job market, and encouraging comprehensive economic development.